The spatial impact of rural economic change on river water quality. (April 2021) - O'Donoghue, Cathal; Buckley, Cathal; Chyzheuskaya, Aksana; Green, Stuart; Howley, Peter; Hynes, Stephen; Upton, Vincent; Ryan, Mary
Highlights: This study combines water quality, land use and environmental data to examine their impact on water quality in rural areas across space and time. This analysis shows that the land uses with the largest negative impacts on water quality are septic tanks and nutrient loads from agriculture. The coefficient on organic N falls significantly between 2002–2011 as the environmental production function of agriculture increased efficient. Solutions will depend on a multi-sectoral approach aimed at addressing the human and land-use factors affecting water quality. The analytical framework provides a tool in the management of risk, allowing for more appropriate land use to restore and maintain water quality. Abstract: This paper, using Ireland as a case study, examines the relationship between rural economic activities and river water quality. The stipulation from the EU water framework directive (WFD) that all surface waters in the EU must be of 'good ecological status' necessitates a quantitative understanding of the major determinants of water quality. Within this context, this paper combines a number of spatial datasets relating to agricultural, land use, residential and industrial activities, to examine the major economic influences on the ecological quality of water resources. It is hoped that providing a comprehensive understanding of the effect of a variety of economic activities that influence the ecological quality of water will be an important tool in the management of risk and will allow for more appropriate land use planning aimed at restoring and maintaining water quality as required by the WFD. Results indicate that the level of forestry, industrial activity, the intensity and type of agricultural activity and the type of wastewater treatment in an area are all critical factors affecting the quality of water resources. The model finds that relationship between agriculture and water quality improved over time during a period where there was substantial legislative measures and financial support to facilitate improved water quality.